Особливості роздільного відбору крові з надниркових вен у діагностиці первинного альдостеронізму - Щекатурова, Л. В.; Черенько, С. М.; Макаренко, Г. І. (Clinical Endocrinology and Endocrine Surgery, 2011)
Modern approach to diagnosis of primary aldosteronism is well described in the article. Methodic and technical difficulties concerning adrenal vein sampling are discussed as well as peculiarities of results interpretation in case of simultaneous subclinical Cushing syndrome. Authors recommend to modify meticulous diagnostic algorithm in patients with suspicious primary aldosteronism by providing of overnight dexametasone test. In the presence of hypercortisolemia results of adrenal vein sampling could be inadequate and this test will be unhelpful. Computed tomography may be more appropriate for lateralization of pathologic adrenal gland in such cases.